Внешнеполитические взгляды вигов-патриотов и тори-лоялистов : памфлеты осени 1774 г. – весны 1775 г. - Дорофеев, Д.В. (Культура народов Причерноморья, 2013)
В исследовании проводится сравнительный анализ внешнеполитических воззрений тори-
лоялистов и вигов-патриотов, получившие распространение в памфлетах, опубликованных между
работой Первого и Второго Континентального Конгресса: октябрь 1774 г. – май 1775 г.
Ключевые слова: генезис внешней политики США, виги-патриоты, тори-лоялисты, Война за
независимость. У дослідженні проводиться порівняльний аналіз зовнішньополітичних поглядів торі-лоялістів
і вігів-патріотів, які були поширені у памфлетах, що друкувалися між роботою Першого та Другого
Континентального Конгресу: жовтень 1774 р. – травень 1775 р.
Ключові слова: генезис зовнішньої політиці США, віги-патріоти, торі-лоялісти, Війна за незалежність. The central issue is to study the genesis of foreign policy of the U.S.A. The purpose of article is study
the foreign policy views of the Tory-Loyalist and Whig-Patriots in the pamphlets published within the period
between the First and Second Continental Congress: October 1774 – May 1775. The following findings were
obtained.
1. Foreign policy views of the Whig-Patriots and Tory-Loyalists had a common base: beliefs in the hostility of
the international environment. The European powers - France and Spain – were planned to take over colonies.
The Whig-Patriots and Tory-Loyalists equally understood the role of the British Colonies in North America
toward Balance of power in Europe and Western Hemisphere: colonies were very important power source for
the future of one of the European Imperia and foothold for continental expansion in the North America.
2. The principal differences of the positions between these two groups lay in the field of understanding of the
British government decisions on the foreign reaction on conflict inside Great Britain. The Whig-Patriots were
convinced that France, Spain, Holland would support the colonies in their confrontation with the mothercountry,
that encouraged the British government to make concessions in the aim of salvation of the imperial
power. The Tory-Loyalists followed the opposite views: as a result of the inability and unwillingness of the
European powers to support the colonies and spoil relations with one of the most powerful Empire, the British
Government suppressed the insurgent colonies in the North America.
3. The debate between the two groups showed that neither the Whig-Patriots nor Tory-Loyalists were out of the
range of ideas that existed in the British colonies after the end of the Seven Years' War.
Key words: genesis of the USA foreign policy, the Whig-Patriots, Tory-Loyalists, the American War of
Independence.